Sosialisasi dan Edukasi Pengolahan Makanan Pendamping ASI (MPASI) untuk Pencegahan Kasus Stunting pada Anak Balita - Linda, Riza; Warsidah, Warsidah (Jurnal Pengabdian kepada Masyarakat Nusantara, 2023)
Complementary foods for breast milk (MPASI) are additional foods given to babies at the age of 6 months. The still high prevalence of stunting cases in Indonesia is a strong warning to always try to promote prevention efforts. The aim of this community service activity (PKM) is to educate residents of the Southeast Pontianak Subdistrict, Pontianak City in processing MPASI porridge so that toddlers have adequate sources of protein, carbohydrates and fat and are free from cases of stunting. The activity was attended by 30 participants consisting of housewives and young women. Delivery of activity material by means of an educational lecture followed by a demonstration of making MPASI porridge in a participant participatory manner. The results of the activity evaluation showed that there was an increase in the ability of activity participants in cooking MPASI porridge as well as an increase in understanding regarding stunting including the causal factors and prevention efforts